Derivados de benzotiazol como inibidores do ciclo replicativo do vírus chikungunya - Leite, Shiraz Feferbaum (2024)
Chikungunya virus (CHIKV) is the causative pathogen of Chikungunya Fever (CHIKF). It has become a major health problem mostly in tropical countries and remains as a neglected and reemergent disease. The treatment is based on palliative measures to control symptoms such as fever, headache, and exanthemas, which further can become chronic and initiate polyarthralgia that may lead to arthritis. Since there are no licensed drugs to treat CHIKF, the search for therapies is essential. In this sense, we aimed to screen twenty synthetic sulfonamides derivatives against CHIKV-nanoluc in vitro with the primary goal of identifying novel inhibitors. Among these compounds, thirteen are heteroaromatic derivatives containing thiazole, benzimidazole, and benzothiazole (BTA) moieties, while seven are sulfonamides containing ester and carboxylic acid groups.. BTA derivatives 6, 9, 11 and 13 exhibited the most potent inhibitory activity based on dose-response assays with EC50 values ranging from 14.9 to 63.1 µM.. These compounds displayed selective index (SI) of 13.8, 5.8, 4.4, and 11.0, respectively. Furthermore, all of them demonstrated post-entry activity, inhibiting CHIKV replication in up to 98%. Interestingly, compound 9 displayed antiviral effect on different stages of viral replicative cycle, such as virucidal (55%), pre-treatment (69%), and entry (98%). The molecular docking analysis revealed the highest affinity scores between these BTA derivatives and the non-structural proteins of CHIKV. Additionally, given that 9 also exhibited inhibitory action on viral entry to the host cells, molecular docking was also conducted with the envelope glycoprotein of CHIKV, yielding a -8.01 kcal/mol score. Infrared spectroscopy analysis corroborated the effect of 9 on virus particles, by indicating interaction with the glycoprotein complex and lipids. The data presented here can provide a source for future in vivo and clinical research in the development of treatments for CHIKF.